Association between COVID-19 and outstanding academic performance at a Spanish university - Fares Amer; Tamara López; Mario Gil-Conesa; Silvia Carlos; Arturo H Ariño; Francisco Carmona-Torre; Miguel A. Martínez-González; Alejandro Fernandez-Montero (BMC, 2023)
Abstract Background SARS-CoV-2 is the causative agent of COVID-19 identified in December 2019, an acute infectious respiratory disease that can cause persistent neurological and musculoskeletal symptoms such as headache, fatigue, myalgias difficulty concentrating, among others including acute cerebrovascular disease with a prevalence of 1-35%. The aim of this study is to evaluate the impact of COVID-19 in undergraduate students on their academic performance as an indicator of their intellectual ability and performance in a university that maintained 100% face-to-face teaching during the 2020-2021 academic year. Methods A total of 7,039 undergraduate students were analyzed in a prospective cohort study at the University of Navarra. A questionnaire including sociodemographic and behavioral questions was sent. PCRs were performed throughout the academic year for the diagnosis of SARS-CoV-2 infection and students' academic results were provided by the academic center, adjusted descriptive and multivariate models were performed to assess the association. Results A total of 658 (9.3%) participants were diagnosed with COVID-19, almost 4.0% of them achieved outstanding academic results, while uninfected students did so in 7.3%. SARS-CoV-2 infection was associated with a significant decrease in having outstanding academic results (OR = 0.57; 95% CI: 0.38-0.86). Conclusion Having COVID-19 disease, decreased academic performance in undergraduate students. Therefore, it is necessary to prevent infection even in the youngest sections of the population.